2016
DOI: 10.4103/0971-5851.180143
|View full text |Cite
|
Sign up to set email alerts
|

Palmar-plantar erythrodysesthesia: An uncommon adverse effect of everolimus

Abstract: Mammalian target of rapamycin inhibitor everolimus is a novel agent used in endocrine therapy resistant hormone receptor positive metastatic breast cancer. Its use has been associated with clinically significant improvement in the otherwise dismal outcomes of this subset of patients. Rash is a common adverse effect associated with everolimus. However, Hand-foot syndrome is an uncommon toxicity with the use of this drug. We report a case of Grade 3 hand-foot syndrome following institution of everolimus therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been reported that HFS is an uncommon toxicity induced by everolimus, and according to its package insert, everolimus has a lower incidence of DIHFS than other protein kinase inhibitors. 35 In Therapeutic Advances in Drug Safety 13 addition, unlike other drugs, everolimus does not inhibit the vascular endothelial growth factor receptor (VEGFR) itself. Instead, it inhibits the production of VEGF and mainly acts as a selective immunosuppressant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HFS is an uncommon toxicity induced by everolimus, and according to its package insert, everolimus has a lower incidence of DIHFS than other protein kinase inhibitors. 35 In Therapeutic Advances in Drug Safety 13 addition, unlike other drugs, everolimus does not inhibit the vascular endothelial growth factor receptor (VEGFR) itself. Instead, it inhibits the production of VEGF and mainly acts as a selective immunosuppressant.…”
Section: Discussionmentioning
confidence: 99%